Key factors and mechanisms of microplastics’ effects on soil nitrogen transformation: A review - Shutao Wang; Wanqing Wang; Sashuang Rong; Guiming Liu; Yuxin Li; Xinxin Wang; Wei Liu (Soil & Environmental Health)
It is indisputable that microplastics (MPs) can profoundly alter nitrogen transformation in soil. However, it remains poorly understood how MPs impact soil nitrogen processes. This review systematically analyzed literature published in recent years related to the impact of MPs on nitrogen transformation. After reviewing the environmental behavior of MPs in soil media, the mechanisms of action and key factors of MPs’ effects on soil nitrogen transformation are elucidated. The size, shape, concentration, and type of MPs significantly alter nitrogen transformation. When MPs enter the soil, they can significantly affect the habitat and diversity of soil microorganisms and the transformation of soil nitrogen by adsorbing pollutants, releasing additives, and altering the physicochemical characteristics of the soil. As organic substrates, MPs can directly affect microbial community structure by promoting microbial colonization. Besides, MPs can also be toxic to soil microorganisms by coming into direct contact with cell surfaces. Microorganisms, key enzymes, and functional genes associated with nitrogen transformation respond to the presence of MPs, thereby affecting the nitrogen conversion process. At the last, measures to mitigate soil MPs contamination are suggested. The article highlights the effects of MPs on soil nitrogen transformation factors, leading to valuable insights into microbially-mediated nitrogen transformation processes in MP-contaminated soils. It offers useful information for determining nitrogen regulation and assessing ecological risks in soils contaminated by MPs.